Proceedings of the Workshop on Computational Semantics Beyond Events and Roles 2018
DOI: 10.18653/v1/w18-1303
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Sarcasm is Extremely Easy ;-)

Abstract: Detecting sarcasm in text is a particularly challenging problem in computational semantics, and its solution may vary across different types of text. We analyze the performance of a domain-general sarcasm detection system on datasets from two very different domains: Twitter, and Amazon product reviews. We categorize the errors that we identify with each, and make recommendations for addressing these issues in NLP systems in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Social media messages, especially from strictly character restricted platforms such as Twitter, are of primary concern, given their often short sparse nature and lack of context. This is to some extent empirically illustrated in the work by Parde and Nielsen (2018), where sarcasm detection over Amazon reviews, compared to Twitter, is substantially more accurate due to the longer length of content and hence richer context available to the sarcasm detection model. Another implication stems from our observation of a very high proportion of url links (80%) seen among humorous tweets, as well as sarcastic (41.56%) and ironic tweets (49.50%).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Social media messages, especially from strictly character restricted platforms such as Twitter, are of primary concern, given their often short sparse nature and lack of context. This is to some extent empirically illustrated in the work by Parde and Nielsen (2018), where sarcasm detection over Amazon reviews, compared to Twitter, is substantially more accurate due to the longer length of content and hence richer context available to the sarcasm detection model. Another implication stems from our observation of a very high proportion of url links (80%) seen among humorous tweets, as well as sarcastic (41.56%) and ironic tweets (49.50%).…”
Section: Discussionmentioning
confidence: 88%
“…used sarcasm hashtags to generate their seed dataset, which is a method that, as we show in 'Prevalence of sarcasm and irony: A manual semantic analysis' section in this paper, is rather problematic. Parde and Nielsen (2018) have shown that using sarcastic tweets (the #sarcasm hashtag) and enriching training datasets with additional annotated Amazon product review data can slightly improve the performance of automated sarcasm detection, where the F score improvements reported are 0.58 to 0.59 for tweets and 0.74 to 0.78 for Amazon reviews. Amazon-based sarcasm detection is more accurate than detection on Twitter, primarily due to longer messages.…”
Section: Sarcasmmentioning
confidence: 99%
See 2 more Smart Citations
“…Many previous studies relied on the application of Naïve Bayes for various detection purposes. In the context of this study, Naïve Bayes was commonly used to classify tweets’ polarity (positive and negative; Parde & Nielsen, 2018). Another way of labeling was established by Das et al (2018) who utilized two types of labels (0 and 1) by indicating whether the tweet is sarcastic or not sarcastic.…”
Section: Amlamentioning
confidence: 99%